Novel stacked abrasive grinding and polishing material and preparation process thereof

Through the preparation method of new stacked abrasive polishing materials, the problems of adhesion, burns and unstable roughness during use of traditional materials are solved, and the effects of long life, good heat dissipation performance and stable roughness are achieved.

CN119635544AActive Publication Date: 2025-03-18DONGGUAN GOLDEN SUN ABRASIVES

Patent Information

Application Number
CN202510041736.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-18
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Traditional polishing materials are prone to problems such as adhesion and burn during use, and their roughness is unstable and their lifespan is short.

Method used

The polishing material is polished with a new stacked abrasive material. By pre-aggrating the single-particle abrasive into a fixed shape, and impregnating, back primer coating, primer coating, sand planting and compound glue treatment on the substrate, forming a polishing material with a composite structure.

Benefits of technology

It achieves a polishing and polishing effect with long service life, good heat dissipation performance and stable roughness, with a service life of more than 10 times that of traditional materials, and maintains a stable roughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237166230000101
    Figure BDA0005237166230000101
  • Figure BDA0005237166230000111
    Figure BDA0005237166230000111
Patent Text Reader

Abstract

The invention relates to the field of polymerized abrasives, in particular to a novel stacked abrasive grinding and polishing material and a preparation process thereof. The scheme comprises the following steps: (1) immersing a base material into an adhesive, and preparing a back bottom layer on one surface of the base material after immersion to obtain a pretreated base material; (2) primer coating: coating the primer on the other surface of the pretreated base material to obtain a glued base material; (3) sand planting is conducted, specifically, sand is evenly planted on the primer side of the glued base material, sand planting particles are in a quadrangular frustum pyramid shape, then a layer of composite glue is coated, and a semi-finished product is obtained after drying; and (4) curing preparation: heating and curing the semi-finished product for 6-24 hours to obtain the novel stacked abrasive grinding and polishing material. The novel stacked abrasive grinding and polishing material prepared by the scheme has the characteristics of long service life, good heat dissipation performance and stable roughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer abrasives, and in particular to a novel stacked abrasive grinding and polishing material and a preparation process thereof. Background Art

[0002] Traditional grinding and polishing materials are mostly used in the form of single-layer abrasives for grinding various materials. Traditional grinding and polishing materials have low strength, low thermal conductivity, and poor toughness, which also makes it very easy to cause problems such as adhesion and burning during grinding. In addition, in the early, middle and late stages of grinding, the roughness of the workpiece surface is also very unstable as the abrasive is lost. The emergence of new stacked abrasives can effectively solve or alleviate these problems.

[0003] Since the new type of stacked abrasive is made by pre-agglomerating single-particle abrasive into a fixed shape through a special adhesive, new abrasives are always exposed during the grinding process as the old abrasives fall off. Therefore, during the use of the new type of stacked abrasive grinding and polishing materials, not only is the lifespan more than 10 times that of ordinary materials, but it also maintains a stable roughness.

[0004] CN 111002235 B discloses a novel method for preparing a polymer abrasive, wherein the composite abrasive is mixed evenly to form abrasive powder, and then a binder is added to bond, solidify, and pulverize to form polymer abrasive of different particle sizes, specifically comprising: (1) stirring and mixing the composite abrasive evenly, and grinding it into abrasive powder; (2) adding a binder to the abrasive powder for bonding, and then solidifying; (3) pulverizing the solidified material, selecting a suitable screen to use a vibrating screen to screen the pulverized material, and pulverizing the screened large material again until it is screened into polymer abrasive of the desired particle size; CN 102729158 B discloses an organic binder stacked abrasive and a method for manufacturing emery cloth using the stacked abrasive. The method of the present invention uses organic polymers as binders and abrasive single particle groups as the main body, including active endothermic materials, inorganic endothermic materials, inert grinding aid materials, and lubricating materials as a whole, and uses low-temperature curing to obtain approximately equi-shaped stacked abrasive units; it provides uniformly organized "cold stacked abrasives" for the manufacture of emery cloth and abrasive belts; and also discloses two methods for making stacked abrasives into stacked abrasive emery cloth, one of which is a differential sliding roller flattening machine, which is used to evenly spread the stacked abrasive on the surface of the substrate. When producing new stacked abrasive grinding and polishing materials, the durability of the substrate, the flatness of the sand surface, and the service life of the grinding material are all crucial. The above scheme does not mention these three key points. Summary of the invention

[0005] In order to solve the above problems, the present invention has developed a product with the characteristics of long service life, good heat dissipation performance and stable roughness.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] A method for preparing a novel accumulated abrasive grinding and polishing material comprises the following steps:

[0008] Step (1) Dip-coating: immerse the substrate in the adhesive, dry it at 130°C-180°C after it is wetted, and then apply a 30 μm-100 μm backing layer on one side of the substrate with a backing slurry to obtain a pretreated substrate;

[0009] Step (2) primer coating: coating the other side of the pretreated substrate with a primer having a thickness of 40 μm to 150 μm by scraping, and drying at 70° C. to 140° C. for 70 min to 150 min to obtain a primer-coated substrate;

[0010] Step (3) Sand planting: Sand is evenly planted on the bottom glue side of the glue-coated substrate. The sand particles are in the shape of a quadrangular pyramid and are 0.6mm-2.2mm in size. The sand is distributed at 400g-1000g per square meter. Then a layer of glue is applied. The amount of glue applied is 550g / m 2 -1100 g / m 2 , drying at 70°C-140°C for 70min-150min to obtain a semi-finished product;

[0011] Step (4) curing: the semi-finished product is heated and cured at 70° C. to 160° C. for 6 h to 24 h to obtain a novel stacked abrasive grinding and polishing material;

[0012] The substrate is one of heavy paper, mesh cloth or film substrate;

[0013] In step (1), the adhesive is one or more of polyimide resin, polyurethane resin or acrylic resin.

[0014] This design has the following main features:

[0015] 1. This solution uses heavy paper, mesh cloth or film substrate as the substrate, which has the characteristics of high inter-layer peeling force, high strength and durability. In order to maintain these excellent characteristics, this solution first impregnates the substrate to ensure that the substrate can be fully combined with the backing paint and primer, and to ensure that the grinding material will not be peeled off or deformed due to external forces during use, and the life of the grinding material will not be reduced due to the loss of the substrate; the design of the back bottom layer helps to improve the strength and stiffness of the substrate, and prevents slipping during the grinding process. Even if it is impacted by external forces, the substrate is not easy to deform.

[0016] 2. The base glue thickness, sand-planting particle size, distribution amount, and coating amount of the composite glue designed in this scheme are all related to the performance of the new stacked abrasive grinding and polishing material. If the base glue is too thick, the sand-planting particles will be immersed too much, affecting the grinding efficiency; if the base glue is too thin, the sand-planting particles will be immersed too little, and the particles will easily fall off; if the sand-planting particles are too large, the surface roughness will be too large, which is not conducive to polishing; if the sand-planting particles are too small, the grinding efficiency will be affected. The main function of the composite glue is to further fix the sand-planting particles. If the coating amount of the composite glue is too small, the particles will easily fall off; if the coating amount is too large, the polishing efficiency will be affected.

[0017] 3. The particle shape of this scheme is designed as a tetrahedron. This shape of abrasive has better flatness when making grinding and polishing materials, and fits the workpiece better during grinding. In addition, the bottom surface area of ​​the tetrahedron is large, which is conducive to fixation in the base glue, and the upper surface area is small, which can ensure that the polishing material has continuous sharpness, a long service life and stable surface roughness. In addition, the particles are formed by bonding with abrasive powder by adhesive, and the abrasive is synchronously lost during the grinding process, which improves the efficiency of abrasive polishing. The sand planting method is gravity sand planting. Through the dispersion effect of two baffles, the abrasive lies neatly on the sand planting surface, but due to the difference in particle size of the abrasive itself, it is necessary to cut the abrasive into a cross-section with a uniform flatness through a special grinding method after the base glue is dried to ensure that the abrasive has a stable roughness at the beginning of grinding. The abrasive height is obtained by adjusting the gap.

[0018] Preferably, the film substrate is a polyimide film or a polyethylene terephthalate film with a thickness of 100 μm-200 μm.

[0019] Preferably, the substrate is heavy paper, and the weight of the heavy paper is 250g-400g per square meter.

[0020] Preferably, in step (1), the backing slurry comprises the following components: in parts by weight, 40-100 parts of adhesive A, 5-10 parts of thickener, 0.1-2.0 parts of wetting agent, 5-10 parts of anti-slip agent and 0-20 parts of diluent.

[0021] Preferably, the adhesive A is one or more of polyimide resin, polyurethane resin or acrylic resin; the thickener is one or more of methyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose or hydroxyethyl cellulose; the wetting agent is one of dehydrated sorbitan fatty acid, polyoxyethylene alkylphenol ether or polyoxyethylene fatty alcohol ether; the anti-slip agent is one of calcium carbonate, kaolin or silicon dioxide; and the diluent is water.

[0022] Adhesive A is one or more of polyimide resin, polyurethane resin or acrylic resin. After curing, it has excellent strength and water resistance. The high strength can ensure that the substrate will not be easily deformed during use. The thickener is a cellulose thickener, generally one or more of methyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, and hydroxyethyl cellulose. The thickening principle is to associate with the surrounding water molecules through hydrogen bonds, thereby reducing the space for free movement of particles and further increasing the viscosity of the system. The wetting agent is one of dehydrated sorbitol fatty acid, polyoxyethylene alkylphenol ether or polyoxyethylene fatty alcohol ether. The main function is to reduce the interfacial tension and make the combination of the scraping slurry and the substrate more closely. The anti-slip agent generally uses calcium carbonate, kaolin or silica to improve the thixotropy of the slurry, making it easier to scrape. In addition, it can increase the friction of the substrate and prevent the polishing material from slipping during use. The diluent is water, which is mainly used to adjust the solid content and viscosity of the slurry.

[0023] Preferably, in step (1), the impregnation amount is 30-60 g / m 2 .

[0024] That is, the weight gain after impregnation is 30-60g / m 2 .

[0025] Preferably, in step (2), the primer comprises the following components: in parts by weight, 30-90 parts of adhesive B, 10-40 parts of filler, 0.1-2.0 parts of leveling agent, 0.1-2.0 parts of coupling agent, and 0-40 parts of diluent.

[0026] Preferably, the adhesive B comprises the following components: by weight, 10-20 parts of epoxy resin or phenolic resin, 1-3 parts of polyurethane resin or acrylic resin; the filler is one or more of wollastonite, calcium carbonate, and calcium sulfate; the leveling agent is one of polyether-modified dimethyl polysiloxane, polyester-modified polydimethyl siloxane, or polyester-modified silicone; the coupling agent is one of silane coupling agents KH550 and KH560; the diluent is one or a mixture of water, ethanol, tetrahydrofuran, and ethylene glycol ether.

[0027] The main type of adhesive is epoxy resin or phenolic resin, which is toughened and increased in viscosity by adding polyurethane resin and acrylic resin. Its main function is to tightly bond the substrate and the abrasive together. The filler used is one or more of wollastonite, calcium carbonate, and calcium sulfate. Its purpose is to improve the strength of the primer and reduce the bubbles generated by the volatilization of the solvent during the drying process of the primer. The leveling agent used is one of polyether-modified dimethyl polysiloxane, polyester-modified polydimethyl siloxane or polyester-modified silicone. Its function is to ensure that the primer is spread more smoothly on the surface of the substrate without shrinkage holes or lines. The coupling agent used is one of silane coupling agents KH550 and KH560. Its function is to promote the combination of adhesive and abrasive. The diluent is one or more of water, ethanol, tetrahydrofuran and ethylene glycol ether. Its function is to adjust the viscosity of the adhesive and ensure that the adhesive is more stable during the drying process.

[0028] The coating method is scraping, which eliminates the tunnel texture on the surface of the roller coating method, making the sand surface smoother and more uniform, greatly improving the surface quality of the polished workpiece.

[0029] Preferably, in step (3), the method for preparing the sand-planting particles comprises the following steps:

[0030] Step (a): Cyclone the abrasive powder to obtain a standby powder having an average particle size of less than 10 μm;

[0031] Step (b): by weight, add 1 part of the reserved powder to 1-2 parts of water, add 0.01-0.03 parts of silane coupling agent, grind with a sand mill for 30-60 minutes, dehydrate, dry, then add to 0.3-0.5 parts of binder, and homogenize to obtain a granular slurry;

[0032] Step (c): inject the original slurry of the particle material into the mold, treat it under vacuum conditions for 3 minutes to 5 minutes, heat and cure it at 70°C-160°C for 3-5 hours after slurry filling, and demold to obtain the planting sand particles.

[0033] The particle size of the planting sand particles can be controlled between 0.6mm and 2.2mm, and the strength of a single particle is between 5N and 50N. The mold shape of this solution is a quadrangular pyramid, and it can also be other shapes depending on different needs.

[0034] Preferably, the abrasive powder in step (a) is one or more of zirconium oxide powder, silicon carbide powder, aluminum oxide powder and diamond powder.

[0035] The granular material prepared by this scheme first cyclones the abrasive powder to remove the coarse particles in the powder. The presence of coarse particles will become a source of cracks, reduce the strength of the sand-planting particles, and ultimately reduce the wear resistance of the new stacked abrasive grinding and polishing material. Secondly, the spare powder and the silane coupling agent are finely ground in a sand mill to improve the surface properties of the spare powder, improve the dispersion effect with the adhesive and the bonding strength with the adhesive. The silane coupling agent can be KH550. High-speed stirring, ball milling dispersion and other methods can be used for homogenization in the binder, only for the purpose of making the sand-planting particles have uniform and stable properties. Finally, the vacuum treatment before curing is to expel the air in the granular material slurry in the mold. Air is another factor that reduces the strength of the sand-planting particles.

[0036] Preferably, the adhesive is a ceramic adhesive or a phenolic resin adhesive.

[0037] Preferably, in step (3), the compound glue comprises the following components: 30-90 parts of adhesive C, 20-70 parts of filler, 5-15 parts of heat absorber, 0.1-3.0 parts of dispersant, 0.1-3.0 parts of thixotropic agent, and 0-50 parts of diluent.

[0038] Preferably, the adhesive C is a phenolic resin or an epoxy resin; the heat absorber is one or more of potassium fluoroborate, zinc stearate, calcium stearate, sodium cryolite or potassium cryolite; the filler is one of bentonite, kaolin or fumed silica; the dispersant is one of polyether-modified trisiloxane, polyether-modified polysiloxane or polyether siloxane copolymer; the thixotropic agent is hydrogenated castor oil; and the diluent is one or more of water, ethanol, tetrahydrofuran or a mixture of ethylene glycol ether.

[0039] Adhesive C is phenolic resin or epoxy resin, and its main function is to fix the abrasive. The heat absorber used is one or more of potassium borofluoride, zinc stearate, calcium stearate, sodium cryolite or potassium cryolite, and its purpose is to absorb the heat generated during product grinding, increase the life of the grinding material, and avoid damage to the workpiece due to excessive heat. The filler used is one of bentonite, kaolin and fumed silica, and its purpose is to reduce the solid content of the composite glue, increase the viscosity of the composite glue, reduce the infiltration of the composite glue into the abrasive, and ensure the synchronous loss of the abrasive. The dispersant used is one of polyether-modified trisiloxane, polyether-modified polysiloxane and polyether siloxane copolymer, and its main function is to improve the dispersion of the filler in the adhesive and prevent the filler from settling. The thixotropic agent used is one of hydrogenated castor oil, propylene glycol and gas silicon. Its function is to ensure that the adhesive remains evenly on the surface of the abrasive and can better protect the abrasive when used. The diluent is one or more of water, ethanol, tetrahydrofuran and ethylene glycol ether. Its function is to adjust the viscosity of the adhesive to ensure that the adhesive is more stable during the drying process and does not generate bubbles.

[0040] This proposal also proposes a new type of stacked abrasive grinding and polishing material prepared by the preparation method of the above-mentioned new type of stacked abrasive grinding and polishing material. Structurally, the new type of stacked abrasive grinding and polishing material in this proposal includes: a layer of planted sand particles coated with a composite glue layer, the planted sand particle layer is embedded in a base glue, the base glue is attached to one side of the substrate, and the other side of the substrate is coated with a backing layer. The backing layer mainly plays a supporting role, the base glue and the composite glue fix the planted sand particles to the substrate, and the planted sand particles are the main functional part of grinding and polishing.

[0041] Compared with the existing technology, the technical advantages of this solution are:

[0042] (1) This solution uses heavy paper, mesh cloth or multi-layer film with high inter-layer peeling force, high strength and durability as the substrate of the new type of stacked abrasive grinding and polishing material, and uses impregnation and scraping technology to ensure that the grinding material can have a lifespan and durability that matches the stacked abrasive during use.

[0043] (2) The novel stacked abrasive polishing material of this scheme prepares sand-grained particles with unique shape and strength. Compared with traditional abrasive polishing materials, it has a service life of more than 10 times and has a stable polishing effect before, during and after polishing.

[0044] (3) The present invention adopts a special compound glue formula, which adds special fillers and thixotropic agents, so as to ensure that the glue is a thin layer on the surface of the sand-planting particles and is not easy to penetrate into the abrasive, providing protection and strength for the grinding and polishing of the new type of accumulated abrasive grinding and polishing materials, while ensuring the synchronous loss of materials and grinding effects, and is suitable for grinding and polishing of metals and paint surfaces. DETAILED DESCRIPTION

[0045] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0046] Example 1

[0047] A method for preparing a novel accumulated abrasive grinding and polishing material comprises the following steps:

[0048] Step (1) Dip coating: immerse heavy paper with a weight of 250 g / m2 into acrylic resin, dry it at 130°C after impregnation, and the impregnation amount is 35 g / m2. 2 , then a 50 μm backing layer is applied by blade coating on one side of the heavy paper with the backing slurry to obtain a pretreated substrate;

[0049] The backing slurry comprises the following components: by weight, 100 parts of adhesive A, 5 parts of thickener, 0.5 parts of wetting agent, 5 parts of anti-slip agent and 10 parts of diluent; the adhesive A is a polyimide resin; the thickener is methyl cellulose; the wetting agent is sorbitan fatty acid; the anti-slip agent is a mixture of 3 parts of calcium carbonate and 2 parts of silicon dioxide; the diluent is water;

[0050] Step (2) primer coating: coating the other side of the pretreated substrate with a primer having a thickness of 60 μm by scraping, and drying at 120° C. for 70 min to obtain a primer-coated substrate;

[0051] The primer includes the following components: by weight, 60 parts of adhesive B, 25 parts of filler, 0.5 parts of leveling agent, 0.5 parts of coupling agent, and 10 parts of diluent; the adhesive B is a mixture of 20 parts of epoxy resin and 1 part of polyurethane resin; the filler is a mixture of wollastonite, calcium carbonate and calcium sulfate in a mass ratio of 1:1:1; the leveling agent is polyether modified dimethyl polysiloxane; the coupling agent is silane coupling agent KH550; the diluent is water;

[0052] Step (3) Sand planting: Sand is evenly planted on the bottom glue side of the glue-coated substrate by gravity sand planting. The sand particles are in the shape of a quadrangular pyramid and are 1.2 mm in size. 500 g of sand is distributed per square meter. Then a layer of glue is applied. The amount of glue applied is 600 g / m 2 , drying at 120°C for 80 min to obtain a semi-finished product;

[0053] The compound glue comprises the following components: 60 parts of adhesive C, 50 parts of filler, 10 parts of heat absorber, 1.0 parts of dispersant, 1.0 parts of thixotropic agent, and 20 parts of diluent; the adhesive C is phenolic resin; the heat absorber is a mixture of potassium fluoroborate, zinc stearate and calcium stearate in a mass ratio of 1:1:1; the filler is bentonite; the dispersant is polyether-modified trisiloxane; the thixotropic agent is hydrogenated castor oil; and the diluent is water;

[0054] The method for preparing the planting sand particles comprises the following steps:

[0055] Step (a): cyclone the abrasive powder to obtain a standby powder with an average particle size of less than 10 μm; the abrasive powder is a mixture of zirconium oxide powder, silicon carbide powder, aluminum oxide powder and diamond powder in a weight ratio of 1:1:1:1;

[0056] Step (b): by weight, add 1 part of the reserved powder to 1 part of water, add 0.01 part of KH550 silane coupling agent, mix and grind for 30 minutes with a sand mill, dehydrate, dry, then add to 0.3 parts of a binder, and obtain a granular material slurry after high-speed stirring and homogenization; the binder is a ceramic binder;

[0057] Step (c): injecting the original slurry of the granular material into the mold cavity to form a quadrangular pyramid mold, treating it under vacuum conditions for 5 minutes, heating and curing it at 120° C. for 4 hours after slurry filling, and demolding to obtain 1.2 mm planting sand particles with a single particle strength of 30N;

[0058] Step (4) curing: the semi-finished product is heated and cured at 120° C. for 18 hours to obtain a new type of stacked abrasive grinding and polishing material.

[0059] Example 2

[0060] A method for preparing a novel accumulated abrasive grinding and polishing material comprises the following steps:

[0061] Step (1) Dip-coating: immerse a 150 μm thick polyimide film into a polyurethane resin, dry it at 150°C after dipping, and then scrape a 30 μm backing layer on one side of the polyimide film with a backing slurry to obtain a pretreated substrate. The dipping amount is 55 g / m 2 ;

[0062] The backing slurry comprises the following components: by weight, 40 parts of adhesive A, 8 parts of thickener, 1 part of wetting agent, 7 parts of anti-slip agent and 15 parts of diluent; the adhesive A is acrylic resin; the thickener is one or more of hydroxypropyl methylcellulose; the wetting agent is polyoxyethylene alkylphenol ether; the anti-slip agent is kaolin; the diluent is water;

[0063] Step (2) primer coating: coating the other side of the pretreated substrate with a primer having a thickness of 120 μm by scraping, and drying at 70° C. for 120 min to obtain a primer-coated substrate;

[0064] The primer comprises the following components: by weight, 90 parts of adhesive B, 40 parts of filler, 1.5 parts of leveling agent, 0.8 parts of coupling agent, and 30 parts of diluent; the adhesive B comprises the following components: by weight, 10 parts of phenolic resin and 1 part of acrylic resin; the filler is calcium carbonate; the leveling agent is polyester-modified polydimethylsiloxane; the coupling agent is silane coupling agent KH560; the diluent is ethanol;

[0065] Step (3) Sand planting: Sand is evenly planted on the bottom glue side of the glue-coated substrate by gravity sand planting. The sand particles are in the shape of a quadrangular pyramid and are 1.8 mm in size. The sand is distributed at 1000 g per square meter. A layer of glue is then applied. The amount of glue applied is 1000 g / m 2 , drying at 130°C for 100 min to obtain a semi-finished product;

[0066] The compound glue comprises the following components: 70 parts of adhesive C, 30 parts of filler, 12 parts of heat absorber, 2.0 parts of dispersant, 1.5 parts of thixotropic agent, and 30 parts of diluent; the adhesive C is epoxy resin; the heat absorber is sodium cryolite; the filler is kaolin; the dispersant is polyether modified polysiloxane; the thixotropic agent is hydrogenated castor oil; and the diluent is water tetrahydrofuran;

[0067] The method for preparing the planting sand particles comprises the following steps:

[0068] Step (a): cyclone the abrasive powder to obtain a standby powder having an average particle size of less than 10 μm; the abrasive powder is zirconium oxide powder;

[0069] Step (b): by weight, add 1 part of the reserved powder to 1.5 parts of water, add 0.02 parts of silane coupling agent K550, mix and grind for 30 minutes with a sand mill, dehydrate, dry, then add to 0.5 parts of a binder, and homogenize to obtain a granular material slurry; the binder is a phenolic resin binder;

[0070] Step (c): injecting the original slurry of the particle material into the mold, treating it under vacuum conditions for 3 minutes, heating and curing it at 120° C. for 3 hours after slurry filling, and demolding to obtain the planting sand particles; demolding to obtain the planting sand particles of 1.8 mm, and the single particle strength is 46N;

[0071] Step (4) curing: the semi-finished product is heated and cured at 80° C. for 24 hours to obtain a new type of stacked abrasive grinding and polishing material.

[0072] Example 3

[0073] A method for preparing a novel accumulated abrasive grinding and polishing material comprises the following steps:

[0074] Step (1) Dip coating: immerse the substrate into the adhesive, dry it at 180°C after dipping, and then scrape 80 μm of the backing layer on one side of the substrate with the backing slurry to obtain a pretreated substrate; the dipping amount is 32 g / m 2 .

[0075] The backing slurry comprises the following components: by weight, 70 parts of adhesive A, 9 parts of thickener, 1.6 parts of wetting agent, 6 parts of anti-slip agent and 16 parts of diluent; the adhesive A is acrylic resin; the thickener is sodium carboxymethyl cellulose; the wetting agent is polyoxyethylene fatty alcohol ether; the anti-slip agent is one of silicon dioxide; the diluent is water;

[0076] Step (2) primer coating: a primer with a thickness of 140 μm is applied to the other side of the pretreated substrate, and the primer is dried at 130° C. for 140 min to obtain a coated substrate; the primer comprises the following components: in parts by weight, 70 parts of adhesive B, 30 parts of filler, 0.6 parts of leveling agent, 0.8 parts of coupling agent, and 8 parts of diluent; the adhesive B comprises the following components: in parts by weight, 15 parts of epoxy resin and 1 part of polyurethane resin; the filler is wollastonite; the leveling agent is polyester-modified polydimethylsiloxane; the coupling agent is silane coupling agent KH550; and the diluent is glycol ether;

[0077] Step (3) Sand planting: Sand is evenly planted on the bottom glue side of the glue-coated substrate by gravity sand planting. The sand particles are in the shape of a quadrangular pyramid and are 0.9 mm in size. The sand is distributed at 700 g per square meter. A layer of glue is then applied, and the amount of glue applied is 600 g / m 2 , dried at 100°C for 110 minutes to obtain a semi-finished product; the composite glue comprises the following components: 55 parts of adhesive C, 21 parts of filler, 15 parts of heat absorber, 2.1 parts of dispersant, 2.5 parts of thixotropic agent, and 10 parts of diluent; the adhesive C is phenolic resin; the heat absorber is calcium stearate; the filler is bentonite; the dispersant is polyether modified trisiloxane; the thixotropic agent is hydrogenated castor oil; and the diluent is water;

[0078] The method for preparing the planting sand particles comprises the following steps:

[0079] Step (a): cyclone the abrasive powder to obtain a standby powder having an average particle size of less than 10 μm; the abrasive powder is a mixture of zirconium oxide powder and diamond powder in a weight ratio of 1:1;

[0080] Step (b): by weight, add 1 part of the reserved powder to 1-2 parts of water, add 0.02 parts of silane coupling agent K550, mix and grind for 40 minutes with a sand mill, dehydrate, dry, then add to 0.5 parts of a binder, and homogenize to obtain a granular material slurry; the binder is a ceramic binder;

[0081] Step (c): injecting the original slurry of the granular material into the mold, treating it under vacuum conditions for 4 minutes, heating and curing it at 120° C. for 4 hours after slurry filling, and demolding to obtain 0.9 mm planting sand particles with a single particle strength of 38N;

[0082] Step (4) curing: the semi-finished product is heated and cured at 90° C. for 20 hours to obtain a new type of stacked abrasive grinding and polishing material.

[0083] Comparative Example 1

[0084] It is a commercially available polymer abrasive grinding and polishing material.

[0085] Comparative Example 2

[0086] The difference from Example 1 is that the shape of the planting sand particles is not limited and most of them are irregular particles.

[0087] Comparative Example 3

[0088] The difference from Example 1 is that the base material is not impregnated.

[0089] Comparative Example 4

[0090] The difference from Example 1 is that no backing layer is provided.

[0091] Comparative Example 5

[0092] The difference from Example 1 is that no thixotropic agent is added to the uncoated adhesive.

[0093] Comparative Example 6

[0094] The difference from Example 1 is that in step (3), the distribution of the planting sand is 1100 g / m 2 .

[0095] Comparative Example 7

[0096] The difference from Example 1 is that in step (2), the primer coating thickness is 200 μm.

[0097] Comparative Example 8

[0098] The difference from Example 1 is that in step (2), the thickness of the primer coating is 20 μm.

[0099] Comparative Example 9

[0100] The difference from Example 1 is that in step (3), the adhesive coating is 1200 g / m 2 .

[0101] Comparative Example 10

[0102] The difference from Example 1 is that in step (a), the abrasive powder is not cycloned.

[0103] Performance Testing:

[0104] A grinding belt was prepared by using the novel stacked abrasive polishing material prepared according to the above-mentioned Examples 1-3 and Comparative Examples 1-10, and SUS-304 was ground with the grinding belt. A hard polyester carrier was selected as the carrier of the grinding belt, wherein the size of the grinding belt was 150 mm×2500 mm. The grinding was carried out at a cutting speed (Vc) of 30 m / s and a feed rate (Vf) of 2-3 m / min, with a grinding time of 5 min / time and a grinding number of 10 times. The single grinding amount δM / g, roughness Ra / μm and surface shedding (δm / g, characterized by the mass difference of the grinding material before and after grinding) were detected and recorded. The test results are shown in Table 1.

[0105]

[0106]

[0107] From the data of Examples 1-3 and Comparative Examples 1-10, it can be seen that the accumulated abrasive grinding materials of Examples 1-3 have a smaller attenuation of single grinding amount, that is, they are sharper and more stable, the roughness is basically a stable value, the surface shedding amount is small, and the service life is longer.

[0108] As can be seen from Example 1, the commercially available polymer abrasive grinding and polishing material has a good grinding and polishing effect in the early stage, but the reduction amount is greatly attenuated in the later stage, the roughness gradually decreases, the surface shedding amount first increases and then decreases, and the comprehensive performance is not as good as Examples 1-3.

[0109] In Comparative Example 2, the sand particles are not limited, and there are many irregular particles. Compared with Example 1, it can be seen that although the single grinding amount is large in the first grinding test, the attenuation rate is fast and the surface shedding amount is large. This may be due to the uneven shape and size of the surface particles, resulting in unbalanced surface force. It also reflects the rationality of the tetrahedral shape of this scheme.

[0110] Comparative Example 3 did not perform an impregnation treatment on the base material, resulting in insufficient base material strength and insufficient adhesion with the base glue and the backing layer, which ultimately led to its breakage during the test process; Comparative Example 4 did not make a backing layer and also had the problem of insufficient base material strength, and ultimately failed to complete 10 tests.

[0111] Comparative Example 5 does not add a thixotropic agent, which results in repeated penetration into the sand-planting particles, making the grinding performance unstable.

[0112] In comparative example 6, the distribution density of the sand-planting particles is too high, which results in lower roughness and less single grinding amount. After the 5th test, the amount of sand-planting particles that fall off decreases and the single grinding amount decays more slowly, but the overall performance is not as good as that of examples 1-3.

[0113] Compared with Example 1, Comparative Example 7 has a base glue thickness that is too large. After the third test, the surface roughness decreases, resulting in an accelerated decay of the single grinding amount; Compared with Example 1, Comparative Example 8 has a base glue thickness that is too small, and the sand particles are easy to fall off, so the test cannot be completed; Comparative Example 9 is similar to Comparative Example 7 in that the single grinding amount is small due to the lower roughness.

[0114] Comparative Example 10 did not perform cyclone, that is, the coarse particles in the abrasive powder were not controlled. During the 3rd to 5th tests, many of the sand-planting particles were broken and the test could not be completed.

Claims

1. A method for preparing a novel stacked abrasive grinding and polishing material, characterized in that: The following steps are involved: Step (1) Dip-coating: immersing the substrate into the adhesive, drying at 130°C-180°C after the immersion, and coating a 30 μm-100 μm backing layer on one side of the substrate with a backing slurry to obtain a pretreated substrate; the adhesive is one or more of a polyimide resin, a polyurethane resin or an acrylic resin; Step (2) primer coating: coating the other side of the pretreated substrate with a primer having a thickness of 40 μm to 150 μm by scraping, and drying at 70° C. to 140° C. for 70 min to 150 min to obtain a primer-coated substrate; Step (3) Sand planting: Sand is evenly planted on the bottom glue side of the glue-coated substrate. The sand particles are in the shape of a quadrangular pyramid and are 0.6mm-2.2mm in size. The sand is distributed at 400g-1000g per square meter. Then a layer of glue is applied. The amount of glue applied is 550g / m 2 -1100g / m 2 , drying at 70°C-140°C for 70min-150min to obtain a semi-finished product; Step (4) curing: the semi-finished product is heated and cured at 70° C. to 160° C. for 6 h to 24 h to obtain a novel stacked abrasive grinding and polishing material; The substrate is one of heavy paper, mesh cloth or film substrate.

2. The method for preparing the novel stacked abrasive grinding and polishing material according to claim 1, characterized in that: In step (1), the backing slurry comprises the following components: in parts by weight, 40-100 parts of adhesive A, 5-10 parts of thickener, 0.1-2.0 parts of wetting agent, 5-10 parts of anti-slip agent and 0-20 parts of diluent.

3. The method for preparing the novel stacked abrasive grinding and polishing material according to claim 2, characterized in that: The adhesive A is one or more of polyimide resin, polyurethane resin or acrylic resin; the thickener is one or more of methyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose or hydroxyethyl cellulose; the wetting agent is one of dehydrated sorbitan fatty acid, polyoxyethylene alkylphenol ether or polyoxyethylene fatty alcohol ether; the anti-slip agent is one of calcium carbonate, kaolin or silicon dioxide; and the diluent is water.

4. The method for preparing the novel stacked abrasive grinding and polishing material according to claim 1, characterized in that: In step (2), the primer comprises the following components: in parts by weight, 30 to 90 parts of adhesive B, 10 to 40 parts of filler, 0.1 to 2.0 parts of leveling agent, 0.1 to 2.0 parts of coupling agent, and 0 to 40 parts of diluent.

5. The method for preparing the novel stacked abrasive grinding and polishing material according to claim 4, characterized in that: The adhesive B comprises the following components: by weight, 10 to 20 parts of epoxy resin or phenolic resin, 1 to 3 parts of polyurethane resin or acrylic resin; the filler is one or more of wollastonite, calcium carbonate, and calcium sulfate; the leveling agent is one of polyether-modified dimethyl polysiloxane, polyester-modified polydimethyl siloxane, or polyester-modified silicone; the coupling agent is one of silane coupling agents KH550 and KH560; the diluent is one or a mixture of water, ethanol, tetrahydrofuran, and ethylene glycol ether.

6. The method for preparing the novel stacked abrasive grinding and polishing material according to claim 1, characterized in that: In step (3), the method for preparing the sand-planting particles comprises the following steps: Step (a): Cyclone the abrasive powder to obtain a standby powder having an average particle size of less than 10 μm; Step (b): by weight, add 1 part of the reserved powder to 1-2 parts of water, add 0.01-0.03 parts of silane coupling agent, grind with a sand mill for 30-60 minutes, dehydrate, dry, then add to 0.3-0.5 parts of binder, and homogenize to obtain a granular slurry; Step (c): inject the original slurry of the particle material into the mold, treat it under vacuum conditions for 3 minutes to 5 minutes, heat and cure it at 70°C-160°C for 3-5 hours after slurry filling, and demold to obtain the planting sand particles.

7. The method for preparing the novel stacked abrasive grinding and polishing material according to claim 6, characterized in that: The abrasive powder in step (a) is one or more of zirconium oxide powder, silicon carbide powder, aluminum oxide powder and diamond powder; in step (b), the binder is a ceramic binder or a phenolic resin binder.

8. The method for preparing the novel stacked abrasive grinding and polishing material according to claim 1, characterized in that: In step (3), the compound glue comprises the following components: 30-90 parts of adhesive C, 20-70 parts of filler, 5-15 parts of heat absorber, 0.1-3.0 parts of dispersant, 0.1-3.0 parts of thixotropic agent, and 0-50 parts of diluent.

9. The method for preparing the novel stacked abrasive grinding and polishing material according to claim 8, characterized in that: The adhesive C is a phenolic resin or an epoxy resin; the heat absorber is one or more of potassium fluoroborate, zinc stearate, calcium stearate, sodium cryolite or potassium cryolite; the filler is one of bentonite, kaolin or fumed silica; the dispersant is one of polyether-modified trisiloxane, polyether-modified polysiloxane or polyether siloxane copolymer; the thixotropic agent is hydrogenated castor oil; and the diluent is one or a mixture of water, ethanol, tetrahydrofuran or ethylene glycol ether.

10. A novel stacked abrasive grinding and polishing material prepared by the method for preparing a novel stacked abrasive grinding and polishing material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Organic bond accumulative grinding material and method for preparing abrasive cloth by organic bond accumulative grinding material

    CN102729158B

  • A novel method for preparing polymeric abrasives

    CN111002235B

  • Film sandpaper production method

    CN104511846A

  • Ceramic microcrystal corundum coated abrasive tool special for fiber board and manufacturing method of ceramic microcrystal corundum coated abrasive tool

    CN107553357A

  • Novel abrasive paper structure and preparation method thereof

    CN112571304A

Cited By

  • A polishing material of abrasive accumulation and its preparation process

    CN122723538A